Lingvocultural Types in the British Language Picture of the World - Pospelova, Nadezhda V. (2021)
One of the mainstreams in linguistics at the end of the XXth - beginning of the XXIst century is a linguocultural modeling of linguistic consciousness and communicative behaviour, i.e. the creation of a certain linguocultural archetype. By itself, the term "linguocultural archetype" is an interdisciplinary concept of cultural linguistics, linguistic conceptology and linguistic personology. The authors of the paper consider a linguocultural archetype, on the one hand, as a set of indicators, which make it possible to find a recognizable image of some individual, and on the other hand, reveal the features typical for a social or ethnic group, which is a binding basis for the archetype. The linguocultural archetypes presented in the paper are considered as typified individuals from a certain ethno-social group; they are recognisable by their characteristic features of verbal and non-verbal behaviour and value orientation in the society. The paper deals with conceptual, figurative, value and associative features of British linguocultural archetypes such as "English policeman", and "knocker up".The important indicators of linguocultural archetypes in cognitive consciousness of people are recurrence, associativity and textuality. The recognisability of the linguocultural archetypes "English policeman" and "knocker up" is stipulated by the mentioning of these professions in films, works of writers and artists, as well as in mass media materials.